Representasi Perempuan dan Batik dalam Instagram Museum Batik Indonesia - Putri, Tanty Wulandari (Universitas Djuanda Bogor, 2024)
Women play a crucial role in human life. The figure of women often emerges in various cultural art products created by humans, showcasing their indispensable role in everyday life. Batik represents one of their creations, a symbol of hope within an artwork. This study employs quantitative content analysis, focusing on the official Instagram account of the Indonesian Batik Museum, @mbatik.in. Examining @mbatik.in posts from March 2021 to October 2023 (totaling 235 posts), data collection involved observation, documentation, and encoding. Reliability testing, executed with three coders using a set sample of 217 posts, unveiled predominant themes: the physical self-image aspect appeared 370 times (89.59%), psychic self-image aspect 43 times (10.41%), social image aspect concerning community relationships 344 times (83.29%), and family relationships 17.19%. Forms of representation encompassed Working Women (133 times - 33.84%), Women as Learners (123 times - 31.30%), Women Entertainers (19 times - 4.83%), Women as Male Companions (30 times - 7.63%), Imaginary Women (42 times - 10.69%), Women as Mothers (33 times - 8.40%), Women as Brides (9 times - 2.29%), and Women as Goddesses (4 times - 1.02%).